Leadership in Educational Institutions: Shared Duty and Joint Responsibility - Joanna Ludwika Pękala; Wiktoria Kowalska (Forum Pedagogiczne, 2020)
In the present world changes are inevitable and modern schools will also be presented to them. School principals should, therefore, aim at transforming the institutions into learning organizations, thus gathering people capable of self-reflection and self-improvement. The purpose of this article is to prove that in order to achieve measurable and sustainable success in an educational institution, leadership must be divided between the principal and the teachers. The ability of diagnosing the situation of the institution is also important, as is the drawing of constructive conclusions from the introduced changes, both those successful and those unsuccessful. Knowledge of possible leadership styles can be an inspiration to search for effective solutions in educational practice for headteachers, teachers and external experts who provide support to schools in the process of change.